La motivación y su relación con la comprensión lectora, en el área de inglés, en los alumnos del 3° grado de educación secundaria de la l.E. "Ofelia Velásquez'' del distrito de Tarapoto, en el año 2010 - Santa Cruz Carhuajulca, Doraliza (2010)
The investigation as by objective to determine the relation that exists between the motivation and the reading understanding of the students, in the Área of English, of the Third Degree of Secondary Education of the Educative lnstitution Ofelia Velasquez of the District of Tarapoto, in 201 O. On the basis of this general mission three specific objectives, a central hypotheses and two operational hypotheses were formulated. The information has collected of 67 students, using like instrument a scale of motivation in the English learning of and a test of reading understanding. The collected data have been process by means of descriptive and inferential statistic. The hypothesis contrast has been carried out by means of the comparison of the Coefficient of Correlation of Pearson with the correlation parameters, considering that the relation is direct when the coefficient is positive and the relation is inverse when he is negative. According to the Coefficient of Correlation of Pearson proportional relation between the motivation and the reading understanding of the students in the area of English exists directly.